2009
DOI: 10.1016/j.domaniend.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between genes involved in growth and muscularity in pigs: IGF-2, myostatin, ryanodine receptor 1, and melanocortin-4 receptor

Abstract: In the swine breeding industry, two economical traits are of particular importance in sires, namely, muscle growth and average daily gain (ADG). These traits are quantitative, which implies that they are under the control of multiple genes. Mutations in these genes, associated with either muscularity or growth, are useful quantitative trait nucleotides (QTN) for unraveling genetic variation of these traits and can be used in marker-assisted selection. Until now, QTN involved in muscle growth and/or ADG in pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The interaction between melanocortins and their receptors in the hypothalamus is one of the main neuroendocrine pathways controlling energy balance (Yeo et al , 2000; Wardlaw, 2001). However, some studies have indicated that these genes could also be expressed in the muscle tissue (Stinckens et al , 2009; Li et al , 2010; Larkina et al , 2011; Tyra et al , 2011). Our data show that the mRNA and protein abundance of LEPR and MC4R in the fat BMIL was lower than in the lean BMIL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between melanocortins and their receptors in the hypothalamus is one of the main neuroendocrine pathways controlling energy balance (Yeo et al , 2000; Wardlaw, 2001). However, some studies have indicated that these genes could also be expressed in the muscle tissue (Stinckens et al , 2009; Li et al , 2010; Larkina et al , 2011; Tyra et al , 2011). Our data show that the mRNA and protein abundance of LEPR and MC4R in the fat BMIL was lower than in the lean BMIL.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants of the leptin receptor (LEPR) and the melanocortin 4 receptor (MC4R) genes were reported to be associated with IMF deposition (Mackowski et al , 2005; Ovilo et al , 2005; Bruun et al , 2006; Jokubka et al , 2006; Kim et al , 2006; Piórkowska et al , 2010; Fan et al , 2009, 2010; Li et al , 2010; Switonski et al , 2010). Although LEPR and MC4R are mainly studied in hypothalamus, some reports indicated that they could be expressed in muscle tissue as well (Stinckens et al , 2009; Li et al , 2010; Larkina et al , 2011; Tyra et al , 2011). Global genomics analyses also led to the hypothesis that IMF deposition could be affected by both lipid metabolism and energy metabolism (Liu et al , 2009; Cánovas et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was hypothesized that the ratio of mRNA concentrations between MSTN and IGFs might serve as indicators of muscle mass (Stinckens et al, 2009). In this study, we determined the expression patterns of MSTN and IGF genes in the skeletal muscle of sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity (on average 321.9 ± 44.0 ng/μl) and quality (260/280 ratio between 1.5 and 2) of the obtained DNA were measured using UV-spectrophotometry (Implen GmbH, München, Germany). For analysis of the c.893G N A substitution in MC4R found by Kim et al (2000), forward primer 5′-TTACTCGCCTCAATTTGCAGC-3′ and reverse primer 5′-ACAAATCACAGAGGCCACC-3′ were used for amplification as described by Stinckens et al (2009). Digestion of the resulting PCR product with TaqI (Thermo Fisher Scientific Inc., USA) was carried out using standard conditions.…”
Section: Mc4r Genotypingmentioning
confidence: 99%